Uji Efektivitas Dekontaminasi Masker Bedah Menggunakan Rice Cooker Pada Masker yang Digunakan Mahasiswa Fakultas Kedokteran Universitas Lampung Tahun 2018 - Gliselda, Vika Kyneissia; Soleha, Tri Umiana; Wintoko, Risal; Sidharti, Liana (CV. Jasa Sukses Abadi, 2024)
Since the pandemic, there has been an increase in demand for surgical masks. This causes an increase in waste that is difficult to decompose and requires solutions such as decontamination so that it can be reused. Mask decontamination is currently still being carried out on a large scale and has been standardized. This is a drawback because it is difficult for the community to do. In Taiwan, there is one method of mask decontamination using a rice cooker which is widely available, but there are still many limitations in this research. The aim of this research is to determine the effectiveness of using a rice cooker as a decontamination tool against bacteria on surgical masks. This research was carried out on 20 samples of surgical masks used by students, consisting of calculating the number of colonies that grew before and after decontamination on Brain Heart Infusion Agar (BHI) media, gram staining, culture on blood agar plate media, catalase test and culture on mannitol media. salt agar. The type of bacteria on the surgical mask used is Bacillus sp. (85%) and Staphylococcus epidermidis (15%). The Wilcoxon statistical test regarding the effectiveness of surgical masks before and after showed a p value <0.05. The use of a rice cooker is effective as a tool for decontaminating surgical masks that have been used by students.